#TITLE_ALTERNATIVE# - HERMAN (NIM : 23107021); Pembimbing Dr. Ir. Andi Isra Mahyuddin, INDRIA
One principal aim of kinematics is to design a desirable mechanism of a mechanical system and calculating the position, velocity, and acceleration of the mechanism. An instruction of the mechanism functions begins with a kinematic analysis where all important dimensions of the mechanism are known, interconnections between links are drawn, and the movement of the moving links are known. Kinematic synthesis, on the other hand, starts with a certain movement that must be fulfilled by a mechanism without known dimensions and form. Three simple methods of kinematic synthesis are type synthesis, dimensional synthesis, and analytical synthesis. The fastest, simplest and easiest are type and dimensional synthesis. In using these two methods, the designerÃ‚Â’s skill, intuition, creativity, experience, and observation are needed to decide a problem solving mechanism. Where in an analytic synthesis, problem solving could be accomplished with algebra and could be computed. Problem in this synthesis occurs when there are more desire points than available equations to be solved. Genetic algorithm is characterized by use of simple computational techniques based on random processes. These two characteristics will help in kinematic synthesis when many of the desirable positions make the solution range large and complex computation is needed. Emergence of genetic algorithm is inspired by theories in biology. Many biological terms and concepts are used. As the name states, processes in genetic algorithm are the same as in biological evolution. Kinematic synthesis with genetic algorithm will generate a solution that fulfills the required condition of the design in a relatively short time but not necessarily the best solution. Genetic algorithm could be used in various syntheses by defining the required conditions given by the designer.